PEMERINTAH, PERUSAHAAN DAN MASYARAKAT: STUDI TENTANG KONFLIK SOSIAL BUDAYA DI BUNTU BATU ENREKANG - Mrs Mirnawati (Rayhan Intermedia, 2019)
This research was conducted to find out: (1) What are the considerations of the Regional Government to make Lunjen Village a mining area. (2) What is the background of the PT Arung Bungin conflict in Lunjen Village, Buntu Batu District. (3) What is the socio-cultural impact of the conflict in the development of PT Arung Bungin in Lunjen Village, Buntu Batu District. To achieve these objectives, the researcher uses data collection techniques through observation, interviews, and documentation. The data obtained from the results of the study were processed using descriptive qualitative research methods. The results showed that (1) the consideration of the local government to make Lunjen Village a mining area, the strong foundation of the local government regarding site selection due to several factors, namely the economic impact that would help Enrekang District's Original Revenue increase, open employment opportunities for local communities. (2) The background of the PT Arung Bungin conflict in Lunjen Village, Buntu Batu Subdistrict, the trigger of the conflict in Lunjen Village because the Lunjen Community considers that the entry of PT Arung Bungin in the Lunjen Village area to carry out mining exploration is not in accordance with applicable procedures. (3) The socio-cultural impact of the conflict in the development of PT Arung Bungin in Lunjen Village, Buntu Batu District, the Lunjen Village Community still adheres to the TOBANA Culture (Please help help advise advice). As a result of the construction of a mine by PT Arung Bungin which triggered conflict in the Lunjen community, the TOBANA culture in some of the Lunjen communities began to appear tenuous with each other.